Protein degradation of Lsd1 is mediated by Bre1 yet opposed by Lsd1-interacting lncRNAs during fly follicle development - Chun Ting Lin; Ruei-Teng Ting; Yang-Hsuan Ou; Tzu-Ling Shao; Ming-Chia Lee (iScience, 2024)
Summary: Tissue development, homeostasis, and repair all require efficient progenitor expansion. Lysine-specific demethylase 1 (Lsd1) maintains plastic epigenetic states to promote progenitor proliferation while overexpressed Lsd1 protein causes oncogenic gene expression in cancer cells. However, the precise regulation of Lsd1 protein expression at the molecular level to drive progenitor differentiation remains unclear. Here, using Drosophila melanogaster oogenesis as our experimental system, we discovered molecular machineries that modify Lsd1 protein stability in vivo. Through genetic and biochemical analyses, an E3 ubiquitin ligase, Bre1, was identified as required for follicle progenitor differentiation, likely by mediating Lsd1 protein degradation. Interestingly, specific Lsd1-interacting long non-coding RNAs (LINRs) were found to antagonize Bre1-mediated Lsd1 protein degradation. The intricate interplay discovered among the Lsd1 complex, LINRs and Bre1 provides insight into how Lsd1 protein stability is fine-tuned to underlie progenitor differentiation in vivo.